Photocatalyst systems containing earth abundant elements for photocatalytic H2 or O2 production from water. - Wang, Yabo. (2013)
H2 production from photocatalytic water splitting using sunlight and photocatalysts is a clean and carbon neutral process to meet the energy and environmental requirements in the future. In this study, research was focused on the design and synthesis of visible light-active photocatalyst systems composed of earth-abundant elements for H2 production from water. Besides the H2 production catalyst for the half reaction of water reduction, an O2 production catalyst was also attempted to understand the other half reaction of water oxidation in water splitting.